ANALISIS PSIKOMETRI SOAL OLIMPIADE KIMIA SMA SEDERAJAT DI PROVINSI RIAU - Ardiansyah, Ardiansyah; Aftarina, Riskika (Journal of Chemistry Education and Integration, 2024)
AbstractTest instruments are one of the important factors in assessing a test. Valid and reliable tests are needed to accurately assess students' abilities. This study analyzes the psychometric profile of the Written Ability Test (TKT) questions for the 1st stage of the Chemistry Championship (CC) held by the Chemistry Education Study Program, UIN Sultan Syarif Kasim Riau in 2024. The psychometric tests carried out include empirical validity, reliability, difficulty level, and question discrimination. The instruments tested were 50 multiple-choice questions for the CC TKT stage 1. The questions were tested on 38 CC participants from 7 schools in Riau Province. There were no valid questions based on the validity test with point biserial correlation, the reliability of the questions was in the very high category, the average difficulty level of the questions was moderate, and the question discrimination power was mostly very good and poor.Keywords : Psychometric Analysis, Written Ability Test, Chemistry Olympiad